The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.31258/jnat.16.1.1-9
|View full text |Cite
|
Sign up to set email alerts
|

Produksi Enzim Selulase olehAspergillus niger pada Ampas Sagu

Abstract: Production of cellulase by Aspergillus niger was carried out by growing the cultureson sago waste. Sago waste contains cellulose that has not been used optimally. Cellulose is a polysaccharide consisting of glucose monomers linked by β-1,4glycosides bonds. Glycoside bonds in cellulose can be enzymatically hydrolyzed into glucose with cellulase enzymes. Solid fermentation used to produce cellulase on sago waste as substrate was influenced by pH (3 to 6), moisture content (40% to 85%), and fermentation time (4 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…5.68% (9.34% into 8.66%) indicate microbial activity runs optimally under 50% moisture condition. Moisture takes important part in biosynthesis and enzyme secretion (Idiawati et al, 2014) . Saccharomyces cerevisiae showed secondary activity i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5.68% (9.34% into 8.66%) indicate microbial activity runs optimally under 50% moisture condition. Moisture takes important part in biosynthesis and enzyme secretion (Idiawati et al, 2014) . Saccharomyces cerevisiae showed secondary activity i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Low content of moisture obviously inhibits microbial growth. The moisture plays important role on nutrient transport, chemical process and metabolic activity during fermentation (Idiawati et al, 2014) . Condition in lack of water decreased microbial growth as well as substrate degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Hal ini dikarenakan mikroorganisme mempunyai masa pertumbuhan yang bervariasi. Masa pertumbuhan terdiri dari beberapa fase yaitu: a) Fase lag, yaitu fase penyesuaian sel-sel dengan lingkungan pembentukan enzim-enzim untuk mengurai substrat; b) Fase eksponensial, yaitu fase perbanyakan jumlah sel di mana aktivitas sel sangat meningkat; c) Fase stasioner, yaitu fase dengan jumlah sel yang bertambah dan jumlah sel yang mati relatif seimbang di mana senyawa metabolit sekunder dapat dipanen; d) Fase kematian, yaitu fase dengan jumlah sel yang mati lebih banyak daripada jumlah sel yang hidup [15]. Kurva pertumbuhan Kapang Phanerochaete chrysosporium sebagai berikut: Gambar 2.…”
Section: Hasil Dan Pembahasan 31 Pembuatan Crude Selulase Dari Bahan Berlignoselulosa Menggunakan Kapangunclassified
“…Another study was conducted by Dini and Munifah [31] regarding the production and characterization of enzymes cellulase by bacteria isolated from seaweed obtained optimum pH 5. Research conducted by Idiawati et al [14] on cellulase enzyme production by Aspergillus niger from sago pulp substrate using the SSF method obtained an optimum pH of 5.…”
Section: Optimum Phmentioning
confidence: 99%
“…Aryani [13] reported that isolated and characterized cellulase enzymes by Mucor sp mold with rice straw and corn cob substrates using the SSF method and additives MgSO4.7H2O, KH2PO4, FeSO4.7H2O, CaCl2.2H2O obtained an optimum pH of 5. Idiawati et al [14] produced cellulase enzymes by Aspergillus niger with sago pulp substrate using the SSF method and the addition of MgSO4.7H2O, KH2PO4, CaCl2.2H2O, urea as an additive whose optimum results were achieved at 30°C and pH 5.…”
Section: Introductionmentioning
confidence: 99%